Seismic Vulnerability and Parametric Study on a Bare Frame Building in Nepal - Dumaru, Rakesh; Rodrigues, Hugo; Furtado, André; Varum, Humberto (Frontiers in Built Environment, 2016)
Recent earthquakes have demonstrated a significant contribution of the masonry infill walls in the structural response of the reinforced concrete (RC) buildings. Field observations after the 25th April’s earthquake in Nepal reinforce the conclusion regarding the influence of the infill walls increasing significantly the structural stiffness, which has a direct impact on the natural frequencies of the structure and of structural elements. Firstly, the manuscript focuses on the performance of the infilled RC structures. Secondly, a bare frame existing building in Nepal was studied, modelled and calibrated with results from data collected on ambient vibration tests. The seismic vulnerability of the building and a parametric study was conducted to study the influence of each material properties in the structural response. The influence of the infill masonry walls presence was also evaluated.